Are testicular mast cells involved in the regulation of germ cells in man?. (12th June 2014) - Windschüttl, S.; Nettersheim, D.; Schlatt, S.; Huber, A.; Welter, H.; Schwarzer, J. U.; Köhn, F. M.; Schorle, H.; Mayerhofer, A.
Summary Protease activated receptor‐2 (PAR‐2) is the receptor for the prototype mast cell product tryptase. PAR‐2 expression by cells of the human germinal epithelium was reported, but the exact cellular sites of testicular expression remained unknown. That became of interest, because mast cells, expressing tryptase, were found in the walls of seminiferous tubules of patients suffering from sub‐ and infertility. This location suggested that mast cells via tryptase might be able to influence PAR‐2‐expressing cells in the germinal epithelium. To explore these points, we used testicular paraffin‐embedded sections for immunohistochemistry. PAR‐2‐positive cells were mostly basally located cells of the seminiferous epithelium, namely spermatogonia. Some stained for the receptor for GDNF (GFRalpha‐1), and possibly represent spermatogonial stem cells (SSCs). As true human SSCs could not be examined, we turned to TCam‐2 seminoma cells, expressing PAR‐2 and stem cell markers, including GFRalpha‐1. TCam‐2 cells robustly responded to stimulation with a specific PAR‐2 agonist (SLIGKV) by increased intracellular Ca2+ levels. Recombinant tryptase and trypsin, but not a control peptide (VKGILS) evoked this response, implying functional PAR‐2. Video imaging and caspase 3/7 assays showed that SLIGKV and tryptase prevented spontaneous apoptosis and increased proliferation of TCam‐2 cells. The expression of the marker of pluripotency OCT3/4 was unchanged upon activation of PAR‐2, suggesting that the stem cell‐like character is not changed. Furthermore, human germ cell cancers were examined. A subset of seminoma and carcinoma in situ samples expressed PAR‐2, indicating that yet unknown subgroups exist. Collectively, the descriptive data obtained in human testicular sections, in germ cell cancers and the functional results in TCam‐2 cells imply a trophic role of mast cell‐derived tryptase for human germ cells. This may be relevant for subtypes of human germ cell cancers, and possibly SSCs. It also raises the possibility that PAR‐2 agonists might be useful for the in vitro propagation of human SSCs.